An active alternative splicing isoform of human mitochondrial 8-oxoguanine DNA glycosylase (OGG1). (December 2015) - Furihata, Chie
Abstract Eight alternatively spliced isoforms of human 8-oxoguanine DNA glycosylase (OGG1 ) (OGG1 -1a, −1b, −1c, −2a, −2b, −2c, −2d and −2e) are registered at the National Center for Biotechnology Information (NCBI). OGG1-1a is present in the nucleus, whereas the other seven isoforms are present in the mitochondria. Recombinant OGG1-1a has been purified and enzyme kinetics determined. OGG1(s) in mitochondria have not been fully characterized biochemically until recently. The major mitochondrial OGG1 isoform, OGG1-2a (also named β-OGG1), has also been expressed and purified; however, its activity is unresolved. Recently, we purified recombinant mitochondrial OGG1-1b and found that it was an active OGG1 enzyme. We reported its enzyme kinetics and compared the results with those of OGG1-1a. The reaction rate constant of OGG1-1b 8-oxoG glycosylase activity (k g ) was 8-oxoG:C > > 8-oxoG:T > > 8-oxoG:G > 8-oxoG:A and was similar to that of OGG1-1a under single-turnover conditions ([E ] > [S ]). Both OGG1-1b and OGG1-1a showed high specificity towards 8-oxoG:C. The reaction rate constant of OGG1-1bN -glycosylase/DNA lyase activity (k gl ) was 8-oxoG:C > 8-oxoG:T ≃ 8-oxoG:G > > 8-oxoG:A and that of OGG1-1a was 8-oxoG:C > 8-oxoG:T, 8-oxoG:G and 8-oxoG:A. Thek gl of OGG1-1b and OGG1-1a is one order of magnitude lower than the correspondingk g value. OGG1-1b showed an especially lowk gl towards 8-oxoG:A. Comparable expression ofOGG1 -1a andOGG1 -1b was detected by RT-PCR in normal human lung tissue and lung cell lines. These results suggest that OGG1-1b is associated with 8-oxoG cleavage in human lung mitochondria and that the mechanism of this repair is similar to that of nuclear OGG1-1a. Currently, the other five mitochondrial OGG1 isoforms have not been isolated. I summarize information on OGG1 isoform mRNAs, coding DNA sequences and amino acid sequences that are archived by the National Center for Biotechnology Information.